DRIVING STRESS OF DRIVERS ON NARROWED LANE AND HARD SHOULDER OF MOTORWAYS - Xing, Jian; Hirai, Shoichi (PEOPLE: International Journal of Social Sciences, 2017)
In order to reduce congestion on a section of motorway, a new type of hard shoulder running (HSR) scheme or a tentative 3-lane operation scheme had been in use since October 21, 2011 for the first time in Japan. It is different from those that have been applied in other countries in that it operates all day long, while the latter operates only during peak periods. As a result, traffic congestion was reduced significantly. Nevertheless, before the operation, road operator was slightly worried about the impact of narrowed widths of lanes and hard shoulder on drivers’ stress while driving. The paper evaluates the impact of narrowed lanes and hard shoulder on young and senior drivers’ stress while driving during the operation of the tentative 3-lane scheme by comparing it among normal 3-lane, 2-lane and tentative 3-lane sections.